Bull bellows and bugles: a remarkable convergence of low and high-frequency vocalizations between male domestic cattle Bos taurus and the rutting calls of Siberian and North American wapiti. Issue 3 (2nd September 2017) - Volodin, Ilya A.; Volodina, Elena V.; Frey, Roland
Abstract: Whereas low-frequency bellows (below 200 Hz) have been investigated in detail in both male and female domestic cattle ( Bos taurus ), male high-frequency bugle calls (over 800 Hz) have not been described so far in any large bovid species. In this study, high-frequency bugles and low-frequency bellows were recorded from three crossbred free-ranging domestic cattle bulls and analysed spectrographically. The maximum fundamental frequency of bellows was 113.6 Hz, whereas the maximum fundamental frequency of bugles was 958.4 Hz, ranging from 801 to 1125 Hz in different males. These amazingly high fundamental frequencies of bull bugles are comparable with those reported for Siberian wapiti Cervus elaphus sibiricus, but lower than reported values for some subspecies of North American wapiti Cervus canadensis . The similarity with both Siberian and North American wapiti was also observed in the production of bull biphonic bugles with two fundamental frequencies: the low and the high one. We suggest that bugles of domestic cattle bulls provide an excellent model for comparative research with cervid bugles concerning the mechanism of vocal production and the underlying anatomical and behavioural adaptations.